Epidemiological outcomes and policy implementation in the Nordic countries during the COVID-19 pandemic ... - Hallberg, Adam; Aakjaer, Mia; Aaltonen, Katri; Andersen, Morten; Pedersen, Elisabeth; Hajiebrahimi, Mohammadhossein; Nordeng, Hedvig; Nyberg, Fredrik; Samuelsen, Per-Jostein; Wettermark, Björn (figshare, 2025)
Abstract Background During the initial phase of the COVID-19 pandemic, there was an intensive debate on which strategies would be most effective to minimize the negative societal impact of the pandemic. This study aimed to provide an overview of key epidemiological outcome measures of the disease in the Nordic countries and the subsequent policy implementation that were undertaken to curb the outbreak. Methods Time trends in test-positive infections, hospitalizations, and intensive care unit (ICU) admissions due to COVID-19 as well as COVID-19 mortality and excess mortality were compared between Denmark, Finland, Iceland, Norway, and Sweden. The epidemiological patterns were presented in relation to 13 different policies implemented to a different degree in the countries, eight of which were related to containment and five to health systems policy. A stringency index summarized the intensity of the policies. Data were collected from Our World in Data, the Oxford COVID-19 Government Response Tracker and ...